Strategi Marketing Communication Melalui Sosial Media Instagram Dalam Meningkatkan Citra dan Popularitas Swiss-Belresort Watu Jimbar - Adi Sudharma, Kadek Januarsa; Arista Putri, Putu Della (Ilin Institute, 2024)
This study aims to find out what kind of marketing communication strategy is implemented by Swiss-Belresort Watu Jimbar on Instagram, in order to increase the company's image and popularity. The subject of this study is a Swiss-Belresort Watu Jimbar marketing communication role in product marketing and building brand image and popularity, which are marketed through social media Instagram. This study is based on marketing communication theory. The results obtained are based on the content uploaded on Instagram and interactions with followers, that Swiss-Belresort Watu Jimbar can carry out the appropriate marketing communication concept. However, content creativity is still limited by the rules, so it seems rigid and doesn't follow what the Z Generation loves. Therefore, the solution that can be offered is to give the freedom to create content according to the Z Generation as the target market.